3. SURVEY ON DISEASE PATTERNS OF INPATIENTS AT THE DEPARTMENT OF TRADITIONAL MEDICINE OF THONG NHAT HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Background: Population aging is a global phenomenon that has begun to manifest itself in Vietnam. With the features of various complicated and overlapping diseases, knowing the disease patterns of the elderly aids in determining the best emphasis for the department's development path and overall objectives in the treatment and management of illnesses among the elderly.Objective: Survey on disease patterns of inpatients at the Department of Traditional Medicine of Thong Nhat Hospital in 2023. Methods: A cross-sectional, retrospective descriptive study. The subjects of the study were all medical records of inpatient treatment at the Department of Traditional Medicine, Thong Nhat Hospital from January 1, 2023 to December 31, 2023 with the main disease diagnosed by ICD 10 code.Results: After reviewing 735 hospital admission records, musculoskeletal and connective tissue illnesses accounted for 54.4% of the total, with back pain being the most frequent ailment, and 88% of patients having more than 5 co-morbidities.Conclusions: The Department of Traditional Medicine has a diversified illness pattern, with noncommunicable diseases being the most frequent, followed by musculoskeletal, circulatory, and neurological disorders. Most patients have numerous diseases, resulting in a significant disease burden.
Keywords: Elderly; disease patterns; traditional medicine